2018
DOI: 10.1093/rheumatology/key244
|View full text |Cite
|
Sign up to set email alerts
|

Dose tapering and discontinuation of biological therapy in rheumatoid arthritis patients in routine care – 2-year outcomes and predictors

Abstract: By implementing a clinical guideline, 62% of RA patients in sustained remission in routine care were successfully tapered, including 16% successfully discontinued at 2 years. Radiographic progression was rare. Maximum one bDMARDs, male gender, and low baseline MRI combined inflammation and combined damage scores were independent predictors for successful tapering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…Another limitation is the lack of radiologic evaluation. Recent studies have shown that imaging-detected residual synovitis is a predictor for the risk of disease flare after tapering or discontinuing biological DMARDs [37,[43][44][45]. Nevertheless, the present study provides useful information regarding the treatment strategies of tofacitinib, namely, dose reduction, withdrawal, and restart, in RA patients who have achieved sustained disease control in daily clinical practice.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another limitation is the lack of radiologic evaluation. Recent studies have shown that imaging-detected residual synovitis is a predictor for the risk of disease flare after tapering or discontinuing biological DMARDs [37,[43][44][45]. Nevertheless, the present study provides useful information regarding the treatment strategies of tofacitinib, namely, dose reduction, withdrawal, and restart, in RA patients who have achieved sustained disease control in daily clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…According to the Kaplan-Meier approach, 66% of our patients had experienced disease flares at 12 months. Recent clinical trials and observational studies regarding biological DMARDs, mainly TNF inhibitors, have also suggested that a stepwise tapering strategy until complete withdrawal is preferable to direct withdrawal [30][31][32][33][34][35][36][37]. This strategy seems to be applicable to tsDMARDs such as tofacitinib and baricitinib.…”
Section: Discussionmentioning
confidence: 99%
“…However, US measurements were not accessed in the present study. Recently, the results from the ADOPT guideline (established in the Capital Region of Denmark) have shown that 2/3 of patients with RA in stable remission were able to successfully taper their bDMARDs . Per the ADOPT guideline, bDMARDs were tapered in all RA patients according to a treatment algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…This post‐hoc analysis was based on data from the longitudinal, multicenter, observational cohort ADOPT (A Dose OPTimization of biological therapy) study, using data collected between 8 May, 2013 and 29 September, 2016 from patients with established RA in sustained clinical remission at baseline and in case of a relapse …”
Section: Methodsmentioning
confidence: 99%